DETERMINING THE INITIAL TIME OF MORNING PRAYER USING THE SOUND OF A ROCK'S CROWD - Fikrah, Atina Zahiratul (Fakultas Syari'ah dan Hukum UIN Walisongo, 2024)
Fajr al-ṣādiq is an indication of the entry of Fajr time. Another indication is the sound of a rooster's crowing, which can be predicted based on his biological clock. Apart from that, roosters also have eyes that are sensitive to light, so the rooster crows very loudly in the morning. This research tries to find out what the astronomical conditions are like when roosters start crowing. This research was carried out by direct observation in the field to obtain accurate results. The results of this research are that the sound of a rooster's crowing can be used as an alarm for dawn but cannot be used as a definite reference for the start of dawn because the roosters are busy crowing several moments after dawn.